Clinical Profile of Patients with Epilepsy - Kafle, Dilli Ram; Oli, Krishna Kumar (Journal of Nobel Medical College, 2015)
Epilepsy is a common and diverse disorder with many different causes. Outcomes are varied with 60—70% of newly diagnosed people rapidly entering remission after starting treatment and 20—30% developing a drug-resistant epilepsy with consequent clinical and psychosocial distress. It is a Descriptive Cross-sectional study which was conducted in Tribhuvan University Teaching Hospital from January 2013 to January 2014.A total of 150 patients participated in the study. There was statistically significant association between numbers of seizures before starting medication and the frequency of seizure after starting medication (p<0.001). DOI: http://dx.doi.org/10.3126/jonmc.v3i1.12234 Journal of Nobel Medical College Vol. 3, No.1 Issue 6, 2014, Page: 31-34